Pathological findings and cervical test "Sims-Hühner" - De la Puente Lanfranco, Rafael (2015)
In the 963 cases we have studied, we found 458 pathological necks representing 47.2 percent, with the remaining 505 normal corresponding to 52.8 percent. The presence of cervicitis was the alteration most frequently found: 319 bullrings corresponding to 33.1 percent. This alteration has given 40.83 percent of test "Sims-Hühner" bad. 61.8 percent in cervical mucus was dirty (infected) and lacking in 56.4 percent. The existence of OE punctate we have found in 81 cases corresponding to the 8.4 percent. Of these, 48.2 percent corresponds to test "Sims-Hühner" with bad results; mucus is dirty (infected) at 54.10 percent and poor in 62.5 percent.